2018
DOI: 10.1161/circulationaha.118.033891
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated IL-1β-GM-CSF Axis in Acute Rheumatic Fever That Is Limited by Hydroxychloroquine

Abstract: Background: Acute rheumatic fever (ARF) and rheumatic heart disease are autoimmune consequences of group A streptococcus infection and remain major causes of cardiovascular morbidity and mortality around the world. Improved treatment has been stymied by gaps in understanding key steps in the immunopathogenesis of ARF and rheumatic heart disease. This study aimed to identify (1) effector T cell cytokine(s) that might be dysregulated in the autoimmune response of patients with ARF by group A streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…effects. [210][211][212][213][214][215] These proinflammatory cytokines are a potentially troubling issue in the management of COVID-19. [216][217][218]…”
Section: A Brief Overview Regarding Various Zinc Ionophores and Cytokmentioning
confidence: 99%
“…effects. [210][211][212][213][214][215] These proinflammatory cytokines are a potentially troubling issue in the management of COVID-19. [216][217][218]…”
Section: A Brief Overview Regarding Various Zinc Ionophores and Cytokmentioning
confidence: 99%
“…Unfortunately, in RHD, the immune cells most relevant to its pathogenesis remain unknown. In a recent study, Kim et al reported disruption in the IL-1β granulocyte-macrophage colony-stimulating factor (GM-CSF) cytokine pathway in peripheral blood mononuclear cells from rheumatic fever patients stimulated with heat-inactivated GAS strains and studied gene expression in these cells (89). They identified hydroxychloroquine as an adjunctive therapy that might limit the dysregulation of this pathway.…”
Section: Approaches For Determining Rhd Disease Variantsmentioning
confidence: 99%
“…Therefore, controlling proinflammatory cytokines may be beneficial for COVID-19 patients in the ICU. Interestingly, HCQ treatment has been shown to control the overproduction of IL-1β and GM-CSF in acute rheumatic fever (Kim et al 2018) and to reduce the level of IL-6 in patients with rheumatoid arthritis (Batun-Garrido et al 2018).…”
Section: Inhibition Of Proinflammatory Molecules By Hcqmentioning
confidence: 99%